A Biomechanical Investigation on the Effects of Deep Deltoid Ligament Repair Combined with Flexible and Rigid Syndesmotic Fixation. Issue 1 (January 2022) - Femino, John E.; Hajewski, Christina; Goetz, Jessica E.; Duchman, Kyle R.
Category: Ankle; Trauma Introduction/Purpose: The role of deep deltoid ligament (DDL) repair in the setting of an unstable syndesmotic injury is largely unknown, and the optimal fixation strategy for syndesmosis stabilization is controversial. The purpose of this study was to investigate the effect of an augmented, anatomic repair of the DDL combined with flexible or rigid syndesmotic stabilization using a cadaveric model. Methods: 10 pairs of fresh-frozen through knee cadaveric specimens were used for biomechanical testing which included subjecting the specimens to 5 Nm of external rotation torque while under 750 N of axial compression. Whole-foot rotation angles were measured and rotation and translation of the fibula, tibia, and talus were tracked with optical motion capture. Specimens were tested intact and then after destabilization by sectioning the anterior inferior tibiofibular ligament (AITFL), posterior inferior tibiofibular ligament, interosseous ligament and membrane extending 7 cm proximal to the ankle joint, and both bands of DDL. The intact fibula was a surrogate for an anatomically fixed fibula. Each specimen underwent mechanical testing both with and without DDL reconstruction added to flexible syndesmotic stabilization using a suture button (SB) plus AITFL reconstruction. In the final test, the syndesmosis was rigidly stabilized using a 4.5 mm screw. Results: Destabilization increased the foot rotation under the applied axial load and torque to 170% (+-49%) of that of the intact case. After flexible syndesmotic stabilization (AITFL + SB) foot rotation was 109% (+-26%) of intact condition. Addition of the deltoid ligament reconstruction (AITFL + SB + DD) reduced rotation to 87% (+-31%) of the intact condition. Fixation with a screw alone came closest to the rotation of the intact specimen (93% +- 17% of intact), and like the flexible repair, the addition of DDL reconstruction to the screw increased rotational stability (85% +- 35% of intact). Conclusion: DDL reconstruction provides improved resistance to external rotation stress when added to both flexible and rigid syndesmotic stabilization. Although our results with both the flexible and rigid constructs demonstrated increased constraint to external rotation stress compared to the intact specimen, these results should be thought of as time zero data, and the implants likely experience some creep with early motion and graduated weight bearing. Our demonstration of increased stability with a deltoid ligament reconstruction suggests that this addition may be beneficial for unstable syndesmotic injuries.